Розвиток забудови Верхнього Києва кінця Х — першої половини ХІІІ ст. - Козловський, А.О.; Ієвлев, М.М. (Археологія і давня історія України, 2010)
У статті розглядаються етапи забудови Верхнього Києва у давньоруський час. Статья посвящена вопросам застройки Верхнего
Киева конца Х — первой половины ХІІІ в. На основе анализа письменных и археологических источников
выделяются этапы застройки «Верхнего города», рассматриваются разные виды существовавших фортификационных сооружений. The article is dedicated to the Upper Kyiv urban
area of the end of the 10th — the beginning of the 13th
centuries. According to the written and archaeological
sources, here are proposed the three stages of the building
of the Upper City and presented different types of
the fortifications of that period.